Legal Consequences Of Doctor's Negligence in Making Visum et Repertum and Corpse Autopsis - Mayang Puspitasari; Budi Pramono (Formosa Journal of Applied Sciences, 2023)
The purpose of this study is to examine the actions of forensic doctors that tend to cause medical negligence. This research is a prescriptive research. The results of this study regarding forensic doctors can be qualified as crimes due to negligence, if they provide inappropriate health services to patients. This can be seen through the Standard Operating Procedures or what are called SPOs that doctors use to work. In addition, forensic doctors can be burdened with legal responsibilities, i. e. administrative, civil and criminal from medical law with license revocation, compensation for patient losses due to liability due to default or unlawful acts. And criminal dispute resolution in the local district court with criminal sanctions.